Acute Oxalate Nephropathy Associated with Orlistat: A Case Report with a Review of the Literature - Dhara Chaudhari; Conchitina Crisostomo; Charles Ganote; George Youngberg (Case Reports in Nephrology)
Orlistat is a gastrointestinal lipase inhibitor used for weight reduction in obese individuals. Enteric hyperoxaluria caused by orlistat leads to oxalate absorption. Acute oxalate nephropathy is a rare complication of treatment with orlistat. Herein we report a patient presenting with acute renal failure which improved minimal with intravenous hydration. She was found to have oxalate crystals on renal biopsy. Patient admitted orlistat use over the counter for weight reduction on further questioning. The purpose of this case review is to increase awareness among patients since they are more focused on losing weight. This case also calls for the provider attention to educate patients regarding side effects of orlistat because of easy availability of orlistat over the counter.